ESTILOS DE APEGO Y AUTOESTIMA EN LOS ESTUDIANTES DE TERCERO DE BACHILLERATO DE LA UNIDAD EDUCATIVA BABAHOYO - MEDRANO GUILLEN MARIA ALEJANDRA (2024)
This research aimed to determine the influence of attachment styles on the development of self-esteem in third-year high school students, in order to first identify the predominant attachment style in the population under study, then assess the levels of self-esteem presented by the students and finally recommend recreational activities that promote functional attachment styles and high autonomy for the students. That is why when talking about attachment styles, we refer to the models of emotional behavior that are developed through interpersonal relationships with close people who live together in daily life, these schemes being direct factors that affect the development of individuals' lives. On the other hand, we talk about self-esteem, which is defined as the idealization that a person has of himself, having a great impact on aspects such as self-concept and the perception of his worth; this element directly influences the way we relate to others and the way we face the obstacles that arise in our daily lives. For this study, evaluation techniques and instruments were used, which allowed obtaining reliable results at the time of the study. Among the evaluation instruments are: The Internal Models of Attachment Relationships Questionnaire – Reduced Version (Camir -R) and the Rosenberg Self-Esteem Scale (EAR), which concluded that attachment styles influence the development of students' self-esteem. The results showed that insecure and avoidant attachment styles predominate in the population under study, which significantly influence the negative self-esteem of third-year high school students at the Babahoyo Educational Unit.